ANALISIS KINERJA KEUANGAN UNTUK MENGUKUR KESEHATAN KEUANGAN KOPERASI KSU BMT ARAFAH KECAMATAN BANCAK KABUPATEN SEMARANG - Afandi, Pandi (AMONG MAKARTI, 2014)
Abstract Cooperative in running its effort need the performance evaluation periodical utilize to know the its effort health storey;level. One of performance assessment needed assessment of finance performance as one of yardstick of co-operation efficacy. KSU BMT Arafah Kecamatan Bancak Kabupaten Semarang one of the type of cooperative of service of finance Moslem law by the effort saving and loan unit, in finance of Moslem law of giving of loan to member named by a defrayal which as a rule referred as by murabahah and mudharobah. Rule about performance of finance and finance health relate at regulation of Minister of Cooperative of State and Small And Medium Industry of number 35.3/Per/M.KUKM/X/2007, where Cooperative can be expressed healthy, healthy enough, under the way and indisposed the than 8 aspect. In this research is direct relevant with the finance performance of there is 5 aspect, that is capital aspect, quality of productive asset, efficiency, likuiditas and also aspect of independence and growth. Result of research indicate that the aspect of cooperative capital enter at healthy criterion, aspect of quality of productive asset of cooperative enter the fluent criterion, do not risk but there is potency stuck, the, aspect of cooperative efficiency show the storey;level of efficiency and efficient and good finance health, aspect of likuidity of cooperation finance enter the criterion likuid and enough likuid , aspect of independence and growth of cooperative finance enter the criterion with the asset rentability less, capital rentability by xself and high operational independence. As a whole finance performance at KSU BMT Arafah from year 2011 until with the year 2013 showing storey;level of finance health with the healthy criterion. Matter suggested in this research is the importance of Co-Operation apply the system of asset management of according to standard of Co-Operation Accountancy ( ETAP), improving the quality of resource with the education and training and also try to minimize the defrayal risk by applying principle of elegibility and carefulness in each;every defrayal channeling of member . Keywords: Capital Aspect, Quality Of Productive Asset, Efficiency, Likuiditas, Independence And Growth